Reconstruction of advanced bone defect associated with severely compromised maxillary anterior teeth in aggressive periodontitis: a case report - Kamil, Wisam Alaa; Hilal Abbood Al-Bayati, Lina; Hussin, Akbar Sham; Hassan, Haszelini (BioMed Central, 2015)
Introduction: Aggressive periodontitis is characterized by a rapid rate of attachment loss and bone resorption. Regenerative therapy offers reconstruction of the periodontium; however, certain advanced cases with a questionable prognosis might remain a challenge. We report a successful intervention outcome of a challenging case in the aesthetic zone of a patient with aggressive periodontitis. Case presentation: A 34-year-old systemically healthy Malay woman was referred to the Periodontics Specialist Clinic of the Kulliyyah of Dentistry, International Islamic University Malaysia, with a chief complaint of bleeding gums and mobility of the upper anterior teeth. A diagnosis of localized aggressive periodontitis was made. A thorough non-surgical periodontal treatment was provided, followed by a series of regenerative periodontal surgeries to manage advanced bone defects. A successful treatment outcome with a good prognosis was achieved. Maintenance through the supportive treatment phase showed marked bone gain. Conclusions: Teeth with severely compromised periodontium of unpredictable prognosis can still be maintained with satisfactory restoration of the function, support, and aesthetics, despite the baseline unpredicted treatment outcome. Proper selection of an advanced periodontal treatment plan can exclude the option of tooth extraction or prosthetic replacement.